Migration of Tinuvin P, a UV stabilizer, from PET bottles into fatty-food simulants - Monteiro, Magali [UNESP]; Nerin, C.; Reyes, FGR (Wiley-Blackwell, 1999)
Tinuvin P migration from Polyethyleneterephthalate (PET) bottles was investigated using several fatty-food simulants such as olive oil, soybean oil, n-heptane and iso-octane, at exposure conditions of 2-10 days at 40 degrees C (total immersion). The stability of several UV stabilizers (BHT, Cyasorb UV 5411, Tinuvin P, Tinuvin 326 and Tinuvin 327) in n-heptane and iso-octane was also studied. After 10 days at 40 degrees C, losses of 6% and 20% in iso-octane and n-heptane respectively, were verified for Tinuvin P. Other UV stabilizers at the same experimental conditions showed higher losses (up to 30% for Tinuvin 327). These results confirm that, when carrying out specific migration studies, the stability of the substance of interest should be established in the food simulant to avoid underestimating the real migration behaviour. In order to quantify UV stabilizer migration, n-heptane and iso-octane solutions were concentrated and directly analysed by SIM mode GC-MS. For olive and soybean oils, Tinuvin P was isolated using size-exclusion chromatography and quantified by SIM mode GC-MS. Iso-octane proved to be a move suitable fatty-food simulant than n-heptane for the migration study of Tinuvin P from PET. Higher levels of Tinuvin P migrated to olive and soybean oils rather than to n-heptane. These results suggest that the MERCOSUL recommended official methods for specific migration studies should be revised since the migration levels using n-heptane as a fatty-food simulant could be underestimated when compared to edible oils. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: migration; fatty-food simulant; UV stabilizers; PET bottles; GC-MS analysis